Smoking status, sports participation and mortality from coronary heart disease. Issue 4 (4th October 2007) - Noda, H; Iso, H; Toyoshima, H; Date, C; Yamamoto, A; Kikuchi, S; Koizumi, A; Kondo, T; Watanabe, Y; Wada, Y; Inaba, Y; Tamakoshi, A; et al.
Abstract : Background: Since smoking and exercise have opposite effects on coronary risk factors, the hypothesis was proposed that smoking might weaken the protective effect of exercise on prevention of coronary heart disease. Objective: To determine the effect of smoking on the relationship between sports participation and mortality from coronary heart disease. Design: Population-based prospective cohort study in Japan. Participants: A total of 76 832 Japanese men and women, aged 40–79 years with no history of stroke, coronary heart disease, or cancer, completed a self-administered questionnaire between 1988 and 1990. Main outcome measures: Systematic mortality surveillance was carried out through 2003, and 638 deaths from coronary heart disease (496 myocardial infarction) were identified. Results: People who reported the longest time in sports participation (⩾5 hours/week) had an approximately 50–80% lower age-adjusted risk of mortality from coronary heart disease compared with those in the second lowest category (1–2 hours/week) among never and ex-smokers, but no association was found among current smokers. Adjustment for known risk factors and exclusion of subjects who died within 2 years of the baseline inquiry did not substantially alter these associations. The multivariable hazard ratios (95% confidence interval) of coronary heart disease for the ⩾5 hours/week versus 1–2 hours/week of sports participation were 0.44 (0.23 to 0.86) among never smokers, 0.18 (0.05 to 0.60) among ex-smokers, and 0.82 (0.47 to 1.40) among current smokers. Similar associations were found for men and women. Conclusions: Smoking may reduce the beneficial effect of sports participation for reduction of fatal coronary heart disease.